An Overview of Social Pluralism in Umayyad Reign: In the light of the Teachings of Prophet (SAW) - Aisha Sadaf; Muhammad Asif (jihat-ul-islam, 2020)
In this article we discuss the relationship of Umayyad rulers with the general society. Due to their behavior, the Ḏimmīs lived a life of comfort and tranquility with great protocol. Actually The Prophet Muhammad (صلى الله عليه وسلم (designed the state system on the basis of social pluralism and made the society of that time a social pluralistic society. Social pluralism is still a big problem in Europe which it has not solved till today but Prophet Muhammad (صلى الله عليه وسلم (have solved the problem of social pluralism, in His time, people of all religions (Jews, Christians, hypocrites, infidels, slaves and masters, rich and poor, Muslims and non-Muslims) of the society were free to adhere to their respective religions irrespective of religion and nationality. Similarly, in the Rightly Guided Caliphate, there are no religious differences anywhere in the society. The same social pluralistic society, which was founded by the Holy Prophet (صلى الله عليه وسلم(, continued as usual. The same process continued in the Umayyad period. The political benevolence and respect accord of the Muslim rulers resulted in the nonMuslim subjects blindly trusting their non-religious rulers and turning to them for their religious disputes, considering them as defenders of their rights.